Translating learning from simulation to clinical: a narrative study of nursing students’ experiences - Watson, Adrianna L.; Young, Chelsey D.; Thomas, Daphne; Tapp, Daluchukwu Megwalu; Holyoak, Saydie; Gardner, Tali (Teaching and learning in nursing, 2025)
What is Currently Known About This TopicSimulation-based learning in nursing education enhances clinical skills, critical thinking, and preparedness, but challenges remain in transferring these skills to real-world clinical settings.What the Paper Adds to the Existing KnowledgeThis study provides a narrative analysis demonstrating how Kolb's Experiential Learning Theory contextualizes the translation of knowledge from simulation and to real-world clinical settings.How the Information in Your Manuscript Can Be Applied to PracticeIncremental exposure to clinical settings, emotional resilience training, realistic simulations, and continuous reflective practice can all improve nursing students' transition from simulation to real-world clinical settings. Simulation in nursing education significantly impacts clinical practice. However, transitioning experiential learning from simulated environments to real-world clinical settings can be challenging for nursing students. This study aims to explore nursing students’ experiences in simulation and their application of learned skills in real-world clinical settings. The authors employed a narrative study design involving nursing students as participants. Data were collected via semi-structured, recorded interviews. Narrative analysis was conducted to interpret the experiences within the framework of Kolb's Experiential Learning Theory. Key findings revealed that simulation effectively prepared students for clinical practice by enhancing their ability to recognize and respond to adverse events and cope with unexpected outcomes, increasing preparedness, and improving leadership skills. The narratives highlighted the continuity of learning from simulation to clinical setting application. The study underscores the importance of simulation in nursing education and its role in helping students transfer knowledge from simulation to real-world clinical experiences. The findings suggest practical implications for educators to enhance simulation-based learning and to support effective transitions to clinical settings.